2021
DOI: 10.1055/a-1540-5378
|View full text |Cite
|
Sign up to set email alerts
|

Zum Ertrag der Unterbringung in einer Entziehungsanstalt und zu methodischen Einwänden gegen die Essener Evaluationsstudie

Abstract: ZusammenfassungDer Bewährungserfolg einer Gruppe ehemaliger Patienten des § 64-Maßregelvollzugs und einer gematchten Vergleichsgruppe von Strafgefangenen wurde nach Entlassung in die Freiheit anhand von BZR-Auskünften verglichen. Methodik 16 Kliniken übermittelten zu mehreren Zeitpunkten pseudonymisierte Daten. Zu jedem Patienten des MRV wurde anhand eines Merkmalschemas ein Vergleichsfall im Strafvollzug identifiziert. Ergebnisse Beim Vergleich der Bewährungsverläufe über mehr als 4 Jahre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…Men were more likely to have a negative treatment outcome in Franke et al ( 40 ) and Hartl ( 37 ); though no significant difference was observed in Berthold and Riedemann ( 17 ). Patients with a migration background were less likely to be successfully discharged from services ( 60 ). Berthold and Riedemann ( 17 ) found no link between age and treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Men were more likely to have a negative treatment outcome in Franke et al ( 40 ) and Hartl ( 37 ); though no significant difference was observed in Berthold and Riedemann ( 17 ). Patients with a migration background were less likely to be successfully discharged from services ( 60 ). Berthold and Riedemann ( 17 ) found no link between age and treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Educational and vocational variables were examined, with evidence of association with treatment outcomes mixed. Patients with successful treatment outcomes were more likely to have completed job training in three studies (37,47,61), but five studies reported that this relationship was non-significant (17, 26,48,51,57). Three studies found that treatment completion was associated with having obtained a high school degree (32,37,47); while three studies led by Schalast found this not to be the case (48,51,57).…”
Section: Social and Demographicmentioning
confidence: 99%
See 2 more Smart Citations
“…Hier werden entsprechende Personen in Gefängnissen betreut [29]. Zur Wirksamkeit der Behandlung suchtkranker Rechtsbrecher im Maßregelvollzug in Bezug auf Suchtmittelkonsum und zukünftige Straffreiheit liegen wenige Studien vor [9,14,[23][24][25]. Die Abbruchquoten im Maßregelvollzug sind mit bis zu 50 % hoch [4,17] und die Definition aussagefähiger Prädiktoren zum Therapieerfolg sehr schwierig.…”
Section: Im Deutschenunclassified